2013
DOI: 10.3109/00016489.2013.831479
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of pulsatile tinnitus caused by sigmoid sinus diverticulum and wall dehiscence: a study of 54 patients

Abstract: The study population comprised 51 females and 3 males. Most patients with PT caused by SSD and SSWD were middle-aged women. All had normal otoscopy results. Anomalies occurred in or adjacent to the region of the transverse-sigmoid sinus junction in 52 patients. Half of the patients (27/54) presented abnormal results of examination of blood lipids. There were 57.41% (31/54) cases with ipsilateral dominance of the venous system, 9.26% (5/54) cases with contralateral dominance, and 33.33% (18/54) cases with co-do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 13 publications
4
56
2
Order By: Relevance
“…Wang found that PT patients with SSDD had a high prevalence of dyslipidemia [30], which can increase the density and viscosity of the blood and elevate the pressure within the sigmoid sinus cavity and against the sigmoid sinus wall. Notably, most of the PT patients (29/33) with SSDD were female in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Wang found that PT patients with SSDD had a high prevalence of dyslipidemia [30], which can increase the density and viscosity of the blood and elevate the pressure within the sigmoid sinus cavity and against the sigmoid sinus wall. Notably, most of the PT patients (29/33) with SSDD were female in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Sigmoid plate dehiscence (SPD) with or without sigmoid sinus diverticulum (SSD), accounting for approximately 1 % of asymptomatic individuals [8,9], has been reported as a treatable cause of PT [10][11][12][13][14]. SPD with SSD (also known as sigmoid aneurysm) was found in about 20 % of PT patients [10,15].…”
Section: Introductionmentioning
confidence: 99%
“…In about half the cases, the SSD is present on the side of the dominant transverse sigmoid sinus, being at least 3 mm larger than the other [3]. This condition is reported more commonly in middle-aged women [3].…”
Section: Discussionmentioning
confidence: 99%
“…In about half the cases, the SSD is present on the side of the dominant transverse sigmoid sinus, being at least 3 mm larger than the other [3]. This condition is reported more commonly in middle-aged women [3]. It is due to dehiscence of the wall of the sinus and protrusion of part of the sinus into the pneumatized bone, resulting in pulsatile and potentially disabling tinnitus [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation